PELAKSANAAN PROMOSI PAKET WISATA UMROH DI PT. ILA SAFINATIN NAJAH KOTA PEKANBARU - Putri, Elsa Indriani; Yulia, Nur Arini (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to determine the types and implementation of Umrah tour package promotions at PT. Ila Safinatin Najah in Pekanbaru City. PT. Ila Safinatin Najah is an Umrah travel agency in Pekanbaru that offers various Umrah tour packages, including regular Umrah packages, Private/VVIP Umrah packages, Najah Umrah packages, Ramadhan Umrah packages, and Plus Umrah packages. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The results of this study indicate that the company implements five types of promotion mix, namely advertising, sales promotion, personal selling, public relations, and direct marketing. Among these promotion tools, non-print media—especially social media such as WhatsApp, Instagram, and Facebook—are the most frequently used because they reach prospective pilgrims widely and quickly. In addition, personal selling through face-to-face communication and chat communication also becomes an important strategy in building trust with potential pilgrims Key word: types of promotion, promotion implementation, Umrah tour packages, PT. Ila Safinatin Najah